The Efficacy of Acupuncture for Treating Depression-Related Insomnia Compared with a Control Group: A Systematic Review and Meta-Analysis - Dong, Bo (Biomed Res Int, 2017)
Objective. To evaluate the effectiveness of acupuncture as monotherapy and as an alternative therapy in treating depression-related insomnia. Data Source. Seven databases were searched starting from 1946 to March 30, 2016. Study Eligibility Criteria. Randomized-controlled trials of adult subjects (18–75 y) who had depression-related insomnia and had received acupuncture. Results. 18 randomized-controlled clinical trials (RCTs) were introduced in this meta-analysis. The findings determined that the acupuncture treatment made significant improvements in PSQI score (MD = −2.37, 95% CI −3.52 to −1.21) compared with Western medicine. Acupuncture combined with Western medicine had a better effect on improving sleep quality (MD = −2.63, 95% CI −4.40 to −0.86) compared with the treatment of Western medicine alone. There was no statistical difference (MD = −2.76, 95% CI −7.65 to 2.12) between acupuncture treatment and Western medicine towards improving the HAMD score. Acupuncture combined with Western medicine (MD = −5.46, CI −8.55 to −2.38) had more effect on improving depression degree compared with the Western medicine alone. Conclusion. This systematic review indicates that acupuncture could be an alternative therapy to medication for treating depression-related insomnia.